The ordering effects of an n-Si defect structure, induced by high fluences of ions with MeV energies - Gaidar, G.P.; Pinkovska, M.B.; Starchyk, M.I. (Reports of the National Academy of Sciences of Ukraine, 2021)
The results of studies of the structural and optical properties of silicon irradiated with light ions of MeV energies with fluences exceeding 1016 cm–2 are generalized. The structure of silicon irradiated with ions is con ventionally divided into several regions (ion path, braking, and outside the braking region), the kind of which is determined by the type of ions, their mass, energy, and temperature during irradiation. It is established that the irradiation with high fluences of light ions of MeV energies causes the formation of ordered layers in the bulk of silicon at depths up to several hundred microns, associated with defects whose properties differ from those of the matrix. It is shown that, under such irradiation conditions, the nature of the defect formation (the number and width of the revealed ordered linear structures and their location relative to the braking region of ions) depends on the mass and energy of ions, the ion beam intensity, the irradiation temperature, and the crystal properties. The effect of the ordering of defects in the form of stress lines and their propagation outside the braking region was discovered, when silicon was irradiated with ions of both hydrogen and helium. It is found that this effect depends on the irradiation intensity and occurs, only when the beam current density is less than 0.45 μA/cm2. It is established that, for silicon irradiated with helium ions in the region of ion path, characteristic is not the monocrystalline, but fragmentary structure, which has an aggregate of ordered stress lines (associated with defects) located in parallel to the braking band of helium ions, and the braking band consists of voids etched as a continuous layer and in the form of separate clusters. It is revealed that the irradiation of dis location silicon with deuterium ions leads to the movement of dislocations during the irradiation and to their crossing of the deuteron braking line due to the formation of stacking faults.